Do You Walk the Talk in Quality Culture? - Barata, João; Rupino da Cunha, Paulo (Journal of Information and Organizational Sciences, 2015)
We present an action research project to foster quality culture in business processes. The client setting is in the food industry, a vital sector for our society and one of the most regulated in the world. Food production involves auditing throughout the supply chain and a demanding information system (IS), with numerous requirements grounded on the organizational policies. Our ISO2 approach – for joint development of IS and quality management system (QMS) – was tailored with a set of routines and artifacts to promote quality culture in the maintenance process of the selected organization. This contribution enables a graphical visualization of existing gaps between the high-level principles endorsed by an organization and its confirmation: (1) instantiating company policies at process level; (2) contrasting the assessment of the process owner and of the quality auditor; and (3) comparing the desired and the real practices in a specific business process. An audit from a food retail group confirmed the positive outcome of ISO2 approach in what regards the internalization of quality principles while developing the IS. Moreover, we performed a longitudinal evaluation to verify enduring effects of the ISO2 approach in business processes. We gathered evidence that ISO2 can (1) improve process users’ awareness of quality culture; (2) suggest an approach to increase trust in company policies; and (3) contribute to business process improvements.